Penerapan Model Problem Based Learning untuk meningkatkan kemampuan pemecahan masalah matematika peserta didik kelas XI MIA SMA Negeri 4 Gorontalo Utara - Muhamad Ansar Muzakkir (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2021)
This study aims to improve the problem-solving ability of students in mathematics. The type of research is classroom action research (CAR) which is carried out in the odd semester of the 2019/2020 academic year with the research subject in class XI MIA 1 SMA Negeri 4 Gorontalo Utara. This study uses a Problem Based Learning Model with the number of students who are subject to action being 34 people. The CAR design uses the Kemmis and Taggart models, including planning, action and observation, and reflection. Data collection techniques use observation, questionnaires, and tests. Data analysis used quantitative and qualitative descriptive statistics. The research took place in 2 cycles. The results of data analysis show that in this study the average scores of formative tests in cycle I and cycle II respectively were: 73.76 and 85.12. Based on the minimum completeness criteria (MCC) set by the school, namely 75, then in the first cycle, the students who got a score of 75 were 24 people or 72.7% of the 33 students who attended. In the second cycle who got a score of 75 were 30 people or 88.23% of the 34 students who attended.